2003
DOI: 10.1007/s00415-003-0177-2
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of a thrombosed intracranial aneurysm during arterial thrombolysis

Abstract: Sirs: Presence of an aneurysm known in advance or incidentally identified is not labelled as an exclusion criterion in the accepted protocols for stroke patients considered for thrombolysis [3,4,9]. Taking the presence of asymptomatic aneurysms in 2-5 % of the population into account [11], every twentieth to fiftieth stroke patient scheduled for thrombolysis has an undetected intracranial aneurysm. The appropriate treatment for a patient, who suffers an occlusion of a large brain artery and has an incidental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…8,9,13,14,19 Our study has several practical consequences. First, antithrombotics and fibrinolytics and also intra-arterial therapies should be used with caution for acute ischemic stroke that occurs distal to an intracranial aneurysm because of the risk of bleeding.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…8,9,13,14,19 Our study has several practical consequences. First, antithrombotics and fibrinolytics and also intra-arterial therapies should be used with caution for acute ischemic stroke that occurs distal to an intracranial aneurysm because of the risk of bleeding.…”
Section: Discussionmentioning
confidence: 97%
“…In such cases, arterial reopening may recanalize the aneurysm, sometimes leading to rupture. 14,19 Ideally, when CT or MR imaging depicts an intracranial aneurysm without bleeding, an SAH should be ruled out by CSF spectrophotometric analysis in accordance with published guidelines before a treatment decision. [15][16][17] However, in the context of Thrombosis of an intracranial aneurysm and parent artery with early recanalization (case 9).…”
Section: Discussionmentioning
confidence: 99%
“…IVT was performed in 2 patients 11,12 and IAT in 29 (24 with urokinase [UK], 13-17 4 with tPA, 15,18,19 and one with both UK and tPA 20 ). SICH occurred in 3 patients treated with IAT (2 with UK, one with tPA), with 2 being subarachnoid hemorrhages.…”
Section: Sich After Off-label Thrombolysis (Tables 1 and 2)mentioning
confidence: 99%
“…Recently, Haji et al firstly reported a patient with multiple unruptured IAs suffered massive (and ultimately fatal) SAH following intravenous tPA [4]. Furthermore, one case also showed that intra-arterial thrombolysis may have additional risk of hemorrhages especially when aneurysm was hidden by the occluding clot [7]. …”
Section: Discussionmentioning
confidence: 99%
“…Although anecdotal case reports have indicated IAs might rupture following intravenous or arterial thrombolysis for acute ischemic stroke, a small number of nonrandomized observational researches are yet to produce a statistically significant association [4,5,6,7]. As all of these studies were confounded by small sample sizes, the safety of thrombolysis in acute ischemic stroke patients with unruptured IAs remains presently unknown.…”
Section: Introductionmentioning
confidence: 99%